Students’ Perception on the Implementation of English Week Program in Islamic Boarding School - Ferian Ferian; Finza Larasati; Masagus Sulaiman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Abstract  This research aims to investigate the students’ perception on the implementation of English week program and how was the program applied. The participants were 34 students, the researchers used stratified technique sampling to take four students of each class. The researcher used questionnaire to collect data from participants. The questionnaire consists of 20 questionnaire items. The students have positive perception on the implementation of English week program. it could be seen from the result of questionnaire item number 12 “the students should follow program is applied on English week” where there were 24 students (70%) agreed about the program. Meanwhile,10 students (30%) disagreed about the program.Keywords: English Week, Perception, Speaking